Six Weeks of Massage Therapy Produces Changes in Balance, Neurological and Cardiovascular Measures in Older Persons - Sefton, PhD, A.T.C., C.M.T., JoEllen M.; Yarar, PhD, P.T., Ceren; Berry, PhD, Jack W. (International Journal of Therapeutic Massage & Bodywork, 2012)
Objectives: Falls in older adults represent a primary cause of decreased mobility and independence, increased morbidity, and accidental death. Research and clinical reports indicate that therapeutic massage (TM) may positively influence suggested causative factors. The second in a two-part study, this project assessed the effects of six weeks of TM treatment on balance, nervous system, and cardiovascular measures in older adults. Design: A randomized controlled trial assessed the effects of six weekly 60-minute sessions of TM on balance, cardiovascular, and nervous system measures. Thirty-five volunteers (19 male and 16 female; ages 62.9 ± 4.6) were randomly assigned to relaxation control or TM groups. A 2 × 4 [treatment condition X time (week 1 and 6)] mixed factorial experimental design was utilized for cardiovascular/balance variables assessed at pretreatment baseline, immediate post-treatment, and 20- and 60-minutes post-treatment; nervous system measures were assessed only at pretreatment and at 60-minute follow-up (2 × 2 mixed design). Longterm benefits were assessed by comparing the TM and control groups on pretreatment baseline measures at week six and a follow-up assessment at week seven (2 × 3 mixed design). Setting: Laboratory Intervention: Six weekly 60-minute, full-body TM. Outcome Measures: Postural control/cardiovascular measures were assessed weeks one, six, and seven; pretreatment and immediate, 20- and 60-minutes post-treatment. Motoneuron pool excitability was assessed pretreatment and 60 minutes post-treatment. Results: The TM group showed significant differences relative to controls in cardiovascular and displacement area/velocity after the week six session, with decreasing blood pressure and increasing stability over time from immediate post-TM to 60 minutes post-TM. The TM group revealed lower H-max/M-max ratios 60-minutes post-treatment. Long-term differences between the groups were detected at week seven in displacement area/velocity and systolic blood pressure. Conclusions: Results suggest six weeks of TM resulted in immediate and long-term improvements in postural stability and blood pressure, compared to a controlled condition.